Direct costs of unintended pregnancy in Spain. (August 2015) - Lete, Iñaki; Hassan, Fareen; Chatzitheofilou, Ismini; Wood, Eifiona; Mendivil, Joan; Lambrelli, Dimitra; Filonenko, Anna
Abstract Objective The aim of the study was to estimate the burden and direct medical costs of unintended pregnancy to the public payer in Spain. Methods An economic model evaluating the costs and outcomes of contraceptive use over a 1-year period was constructed for women in Spain aged 15 to 44 years at risk of pregnancy. Model inputs were derived from published literature and national survey data. Outcomes evaluated included: (i) the annual number of unintended pregnancy events and their cost; (ii) the proportion of unintended pregnancy events and their cost due to non-adherence; and (iii) the use and cost of contraceptive methods in Spain. Results Of the total number of pregnancies, 35% are estimated to be unintended and are associated with a direct cost burden of €292.8 million per year. Most unintended pregnancies (26%) occur in women aged 30 to 34 years, whilst 69% of the total cost burden is estimated to be attributable to poor adherence to contraceptive methods. Conclusions The cost associated with unintended pregnancy is high. The major proportion of the burden is estimated to be attributable to imperfect adherence and is likely avoidable. Shifts in patterns of contraceptive use, combined with measures to improve adherence, could have a substantial and positive impact on this burden.